RGB-D terrain perception and dense mapping for legged robots - Belter, Dominik; Łabecki, Przemysław; Fankhauser, Péter; Siegwart, Roland (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the issues of unstructured terrain modeling for the purpose of navigation with legged robots. We present an improved elevation grid concept adopted to the specific requirements of a small legged robot with limited perceptual capabilities. We propose an extension of the elevation grid update mechanism by incorporating a formal treatment of the spatial uncertainty. Moreover, this paper presents uncertainty models for a structured light RGB-D sensor and a stereo vision camera used to produce a dense depth map.
Keywords: RGB-D perception; elevation mapping; uncertainty; legged robots